Penerapan Konseling Kelompok Teknik Direktif untuk Mengatasi Kecemasan KDRT di UPTD PPA Bantul Yogyakarta - Khairunnisa, Astra; Putri, Roza Elmanika; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Many women have experienced domestic violence in the Bantul district of Yogyakarta. Victims of domestic violence at the UPTD PPA Bantul will receive guidance and protection in the form of individual counseling activities from psychologists and legal protection from lawyers who have been provided by the UPTD PPA Bantul. After conducting a psychological examination with clinical interviews, observation, psychological tests, and the administration of the Hamilton Anxiety Rating Scale (HARS), it is known that WBS shows unstable emotional behaviour, restlessness, crying, fatigue, and difficulty sleeping. After implementing group counselling with targeted techniques, the clients already have a goal to overcome the anxiety experienced after being a victim of domestic violence. Understanding and hoping for good from the rehabilitation he is doing will be an asset in the future. Percentage decrease in anxiety, on average, 41%.